A 6 Second Analytical Method for Quantitation of Tacrolimus in Whole Blood by Use of Laser Diode Thermal Desorption Tandem Mass Spectrometry. (1st May 2019) - Merrigan, Stephen D; Johnson-Davis, Kamisha L
Abstract: Background: Therapeutic drug monitoring of immunosuppressive drugs is imperative for organ transplant recipients. High-performance LC-MS/MS is considered gold standard; however, immunoassays provide rapid turnaround time. New technology was developed to reduce mass spectrometry analytical run-time. The laser diode thermal desorption source coupled with tandem mass spectrometry (LDTD-MS/MS) eliminates chromatographic separation to increase analytical throughput. Methods: A rapid, 6 second, LDTD-MS/MS analytical method was developed for the quantification tacrolimus in whole blood. Whole blood samples were lysed, followed by protein precipitation and solid-phase extraction. Extracted samples with desorption solution were spotted onto a LazWell plate then dried and loaded into the LDTD source for analysis with an AB SCIEX 5500 mass spectrometer in positive multiple reaction monitoring mode. The LDTD laser profile ramps from 0% to 65% of full power over 3 s and is held at 65% for 1 s before returning to initial conditions for 2 s. Results: Data presented include tacrolimus by LDTD-MS/MS comparison to LC-MS/MS, sensitivity, imprecision, interference, linearity, and stability. Method comparison between LDTD-MS/MS and a validated in-house LC-MS/MS assay yielded the following: (LDTD-MS/MS) = 1.119 (LC-MS/MS) + 0.23 ng/mL, Sy/x = 1.26, r = 0.9871 (n = 122). The limit of quantification by LDTD-MS/MS for tacrolimus was <0.3 ng/mL and total imprecision was <10%. Conclusions: Laser diode thermal desorption tandem mass spectrometry technology can provide rapid turnaround time to result for tacrolimus. The analytical time for LDTD-MS/MS was 6 s compared to 135 s by LC-MS/MS, a >95% decrease in analytical time.